Being European: Staging the Nation in 1920s Icelandic Theatre - Thorbergsson, Magnus Thor (Nordic Theatre Studies, 2018)
During the campaign for Iceland’s independence in the nineteenth and early twentieth centuries, theatre was considered an important site for the representation of the nation. Emphasis was placed on producing and staging local plays dealing with the nation’s folklore, myths and history, thereby strengthening a sense of the roots of national identity. The article examines the longing for a representation of the nation in late nineteenth-century theatre as well as the attempts of the Reykjavik Theatre Company to stage the nation during the so-called ‘Icelandic Period’ (1907-20), before analyzing the distinctive changes in the company’s repertoire following the decision of the Icelandic parliament to build a national theatre in 1923. The staging of the nation, which had been dominated by nineteenth-century cultural nationalism, took a turn in the late 1920s towards representing the nation as a member of European metropolitan culture through an increased focus on international contemporary drama, bourgeois bedroom farce and classical drama. The image of the modern Icelanders, as represented on the stage in the 1920s, was that of the middle-class bourgeoisie.